Seroprevalence, geographical distribution, and risk factors of peste des petits ruminants in the Republic of Chad - Mahamat, Ouagal; Doungous, Tchari; Kebkiba, Bidjeh; Oumar, Hadjé Arabié; Oussiguéré, Assandi; Yacoub, Adam Hassan; Goudja, Adoum; Guindé, Mahamat; Moussa, Ahmat Hassan (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objective of this study was to determine the prevalence, geographical distribution, and main risk factors for peste des petits ruminants (PPR) in the Republic of Chad. Materials and methods: A total of 3,546 sera collected from unvaccinated small ruminants including 1,699 goats and 1,847 sheep in 19 of the 23 regions in Chad were randomly sampled. The competitive enzyme-linked immunosorbent assay technics were used for serological analysis. Results: The overall seroprevalence at the individual level was 52.9%±1.6% (48.9% for goats and 56.2% for sheep). Seroprevalence observed in the Chari Baguirmi, Ouaddaï, and N’Djamena regions was significantly higher than those in the other regions. Transhumant herds are the most exposed than the sedentary ones. Older animals were more affected than the young ones. Kababich sheep are the most affected than other breeds. Conclusion: This study has shown that the PPR virus is circulating in the Republic of Chad. In view of the results obtained, the disease is enzootic in the country. Epidemiological information obtained including seroprevalence rate, risk factors (sex, breed, age, and mode of rearing), and geographical distribution will help to define an appropriate strategy for PPR control in the Republic of Chad. http://doi.org/10.5455/javar.2018.e293